Neues Konzept zur Bewegungsanalyse und -synthese für Humanoide Roboter basierend auf Vorbildern aus der Biologie - Bauer, Christian (Schriftenreihe des Instituts für Angewandte Informatik - Automatisierungstechnik, Karlsruher Institut für Technologie, 2013)
New methods to generate and analyze motions of humanoid robots are presented and applied to a demonstrator. Reflexes of humans and neural central pattern generators (CPGs) were used as archetype. With leaky Integrate-and-Fire neurons a generic reflex template was designed and put to work for several specialized reflexes. The designed CPGs were used to analyze robotik motion as well as for generation of locomotion patterns on a biped demonstrator.